2020
DOI: 10.1111/jppi.12366
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Findings From a Nationwide, Multicenter Mental Health Service for Adults and Older Adolescents With Autism Spectrum Disorder and ID

Abstract: Background The identification and treatment of psychiatric disorders in individuals with autism spectrum disorders (ASD) and ID presents many challenges. We describe the development of a professional network, together with a standardized protocol for clinical assessment, designed to promote clinical competence and professional development in eight clinical centers responsible for providing mental health services to autistic individuals with ID across all four health regions of Norway. Specific aims to describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 63 publications
1
41
0
Order By: Relevance
“…That study was based on a cohort of individuals with ASD and ID and previously identified psychiatric illness who were selected on the basis that they met strict criteria for the psychiatric disorders diagnosed. For participants such as those in the present study, who comprised a very heterogenous group of individuals with ASD and ID referred for psychiatric assessment, cut-off values may need to be lowered in order better to identify individuals requiring a more focussed psychiatric examination (Helverschou et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…That study was based on a cohort of individuals with ASD and ID and previously identified psychiatric illness who were selected on the basis that they met strict criteria for the psychiatric disorders diagnosed. For participants such as those in the present study, who comprised a very heterogenous group of individuals with ASD and ID referred for psychiatric assessment, cut-off values may need to be lowered in order better to identify individuals requiring a more focussed psychiatric examination (Helverschou et al 2020a).…”
Section: Discussionmentioning
confidence: 99%
“…The AUP (Autism, Intellectual disability and Psychiatric disorder) study is an on-going clinical treatment study that began in 2010 (see Helverschou et al 2020a). It involves eight clinical centres responsible for providing specialist, hospital-level mental health services to individuals with ASD and ID across all four health regions in Norway.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations